Immature neutrophils in cord blood exert increased expression of genes associated with antimicrobial function - Miková, Eliška; Černý, Viktor; Novotná, Olga; Petrásková, Petra; Boráková, Kristýna; Hel, Zdenek; Hrdý, Jiří (Frontiers in Immunology, 2024)
The immune systems of both the mother and the newborn face significant challenges during birth. Proper immune regulation after birth is essential for the survival of neonates. Numerous studies have demonstrated that the neonatal immune system is relatively immature, particularly in its adaptive arm, placing the primary responsibility for immune surveillance on innate immunity. Given the significant role of neutrophils in protecting the neonate after birth, we conducted a study investigating the properties of neutrophils in newborn cord blood. Our findings demonstrate the presence of immature low-density neutrophils in the cord blood, which are likely responsible for the observed elevated expression of genes coding for proteins essential to antimicrobial response, including myeloperoxidase, neutrophils elastase, and defensins. We propose that these cells function normally and support the protection of newborns early after birth. Furthermore, our results suggest that the mode of delivery might significantly influence the programming of neutrophil function. The presented findings emphasize the importance of distinct neutrophil subpopulations in neonatal immunity and their potential impact on early postnatal health.